2016
DOI: 10.1515/jcim-2015-0089
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the Bali Yoga Program (BYP-BC) on reducing psychological symptoms in breast cancer patients receiving chemotherapy: results of a randomized, partially blinded, controlled trial

Abstract: Background Several cognitive behavioral interventions have been reported to reduce psychological symptoms in breast cancer (BC) patients. The goal of this study was to evaluate the effects of a yoga intervention in reducing depression and anxiety symptoms in BC patients. Methods This study was a randomized, partially blinded, controlled trial comparing a standardized yoga intervention to standard care. It was conducted at three medical centers in Montreal, Canada. Eligible patients were women diagnosed with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…Dose varied widely, with classes lasting up to 90 minutes and occurring from 1 to 6 days per week over 1 to 8 weeks. Furthermore, in most studies, home practice was prescribed . For the post‐treatment yoga studies, interventions were designed as gentle stretching and strengthening exercises, including breathing techniques (Pranayama), postures (Asanas), meditation, and relaxation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Dose varied widely, with classes lasting up to 90 minutes and occurring from 1 to 6 days per week over 1 to 8 weeks. Furthermore, in most studies, home practice was prescribed . For the post‐treatment yoga studies, interventions were designed as gentle stretching and strengthening exercises, including breathing techniques (Pranayama), postures (Asanas), meditation, and relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies that were conducted during treatment, several did not report or only partially reported adherence . Some studies reported the mean number of classes attended (eg, 5.5 of 8 possible classes) and mean hours of home practice (eg, 2.25 hours per week) . Others reported adherence ranging up to 81% of participants attending all classes and 100% engaging in 5 to 7 days of home practice per week .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on yoga benefits in cancer patients suffer from heterogeneity with various types of yoga interventions, duration, exposure, practices, and indications. 29 For example, different types of yoga training, such as Bali Yoga, 30,31 Vivekananda Yoga, 32 and Hatha Yoga, 33 among others might have a different influence on the observed effects, but evidence comparing various yoga types is still absent. In addition, the duration, schedules, and frequency of yoga support with or without specialized supervision differed in many published investigations to date.…”
Section: Discussionmentioning
confidence: 99%